Differentiation in practice : a resource guide for differentiating curriculum, grades 9-12 - Tomlinson, Carol A.; Strickland, Cindy A., 1959- (Alexandria, VA : Association for Supervision and Curriculum Development, 2005)
Presents an introduction to differentiated instruction, a systematic approach to planning curriculum and instruction to meet the needs of academically diverse learners, and features annotated lesson plans for differentiated units in a variety of curriculum areas, geared toward students in themiddle grades.
American stories : an English unit on reading and writing historical fiction -- Which comes first, the individual or society? : an English and humanities unit on Macbeth -- Toward disunion, 1854-1861 : a U.S. history unit on the path to the Civil War -- It has to hang : a visual arts unit on 3-d ceramic sculpture -- The eyes of experience : an English unit on perspective and identity -- Point the way : a mathematics unit on vectors -- What goes up must come down : a mathematics unit on quadratics in the general form -- The little prince and me : a world language unit on reading target-language literature -- Water, water, everywhere : an earth science unit on water and watersheds.
Includes bibliographical references (p. 359-362) and index.
Reference and Research Book News.
Professional
Keywords: Curriculum planning -- United States; Education, Secondary -- Curricula -- United States; Individualized instruction -- United States; Curriculum planning -- United States; Individualized instruction; Secondary education -- United States -- Curricula